SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN BIAYA RAWAT INAP MENGGUNAKAN METODE ACTIVITY BASED COSTING PADA RUMAH SAKIT PERMATA BEKASI - Effendi, M. Ridwan (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
The analysis cost units of activity on the unit cost of inpatient services, in order to calculate the total financing required. The purpose of this study was to analyze the determination of the cost of hospitalization in the hospital. Analysis was method used is descriptive analysis to describe the costing method in accordance with the theory and practice of comparing with the existing costing methods. From the analysis carried out that known the price of the rooms that have been determined by the hospital for this type of Rp. 675.000 VVIP room. VIP Rp. 460.000, class I Rp. 260.000, class II Rp. 160.000, and Class III, Rp. 75.000. For the ABC method in the VIP room, I, II and III give the results of the calculation are greater than the price of the rooms that have been determined by the hospital. With the difference in price to the VIP Rp. 592.250, class I Rp. 297.257, class II Rp. 199.649, and for the third class of Rp. 85,075. While the results of the calculation VVIP class Activity Based Costing less than the cost of hospitalization has been deter mined by the hospital. That is the difference of Rp. 620.302. Of the goal should be to show that the determination of the cost of hospitalization in the department of Rumah Sakit Permata Bekasi unaccordance with there sources.